2006
DOI: 10.1126/science.1128657
|View full text |Cite
|
Sign up to set email alerts
|

Storage of Spatial Information by the Maintenance Mechanism of LTP

Abstract: Analogous to learning and memory storage, long-term potentiation (LTP) is divided into induction and maintenance phases. Testing the hypothesis that the mechanism of LTP maintenance stores information requires reversing this mechanism in vivo and finding out whether long-term stored information is lost. This was not previously possible. Recently however, persistent phosphorylation by the atypical protein kinase C isoform, protein kinase Mzeta (PKMz), has been found to maintain late LTP in hippocampal slices. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
735
3
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 769 publications
(789 citation statements)
references
References 25 publications
(38 reference statements)
44
735
3
7
Order By: Relevance
“…The effect of the PKC inhibitor was not restricted to one mouse strain, but was also profound in C57BL/6NCrl mice that typically acquire and generalize strong fear responses (Radulovic et al, 1998b) and exhibit resistance to contextual fear extinction (Stiedl et al, 1999;Siegmund et al, 2005). Together with data showing effects of long-term activation of atypical hippocampal PKC on behavioral performance (Pastalkova et al, 2006), our data suggest that typical PKCs might also contribute to persistent fear-motivated behavior.…”
Section: Discussionsupporting
confidence: 50%
“…The effect of the PKC inhibitor was not restricted to one mouse strain, but was also profound in C57BL/6NCrl mice that typically acquire and generalize strong fear responses (Radulovic et al, 1998b) and exhibit resistance to contextual fear extinction (Stiedl et al, 1999;Siegmund et al, 2005). Together with data showing effects of long-term activation of atypical hippocampal PKC on behavioral performance (Pastalkova et al, 2006), our data suggest that typical PKCs might also contribute to persistent fear-motivated behavior.…”
Section: Discussionsupporting
confidence: 50%
“…It is an atypical PKC enzyme with the ability to be autonomously active once synthesized, thereby stabilizing lasting changes required for sustained LTP. [96][97][98][99] However more recent studies show that PKMz, is dispensable for LTP associated with memory. [100][101][102] In 1998, Tompa and Friedrich put forth the prion theory of memory wherein they suggested that propagation of a non-toxic conformational state of prions could underlie cellular functions like memory storage.…”
Section: Biochemical Models For Ltm Maintenancementioning
confidence: 99%
“…Pharmacological experiments indicate that the atypical protein kinase C known as protein kinase Mζ (PKM-ζ) may be necessary and sufficient for the maintenance of L-LTP in the hippocampus (Ling et al, 2002;Pastalkova et al, 2006) and can also be involved in synaptic tagging . More recently, it has been proposed that CaMKII could also participate in setting synaptic tags for L-LTP capture, whereas MAPKs would play an equivalent role for L-LTD (Sajikumar et al, 2007a).…”
Section: Accepted Manuscriptmentioning
confidence: 99%